2018
DOI: 10.22226/2410-3535-2018-3-282-287
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance and magnetic properties of α-BiNb1−xFexO4−δ

Abstract: Iron-containing ceramic materials based on BiNbO 4 of orthorhombic modification were obtained by solid-phase synthesis. Solid solutions α-BiNb 1−x Fe x O 4−δ were synthesized in the narrow concentration interval of х ≤ 0.03. The single-phase structure of the samples prepared was determined by X-ray diffraction and SEM-analyses. In the electron paramagnetic resonance (EPR) spectra of BiNb 1−x Fe x O 4−δ , a wide band with the center at g = 2.16-2.37 was observed, and a low-intensity signal with g-factor of abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…For example, in Mn-doped GaN systems concentration-independent AFM exchange of the order −1.624 K was observed . Moreover, one can expect in the imperfect areas, the appearance of dimers with positive exchange that, perhaps, some authors observe even at as-prepared state without undesirable phases. , …”
Section: Experimental Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in Mn-doped GaN systems concentration-independent AFM exchange of the order −1.624 K was observed . Moreover, one can expect in the imperfect areas, the appearance of dimers with positive exchange that, perhaps, some authors observe even at as-prepared state without undesirable phases. , …”
Section: Experimental Results and Discussionmentioning
confidence: 98%
“…63 Moreover, one can expect in the imperfect areas, the appearance of dimers with positive exchange that, perhaps, some authors observe even at asprepared state without undesirable phases. 16,64 ■ SUMMARY AND CONCLUSION In summary, a series of TiO 2 :Fe-type samples with different Fe content have been synthesized by a low-temperature sol−gel method and subsequently subjected to the etching in 2 M HCl. It has been shown that etching of the samples in hydrochloric acid completely removes impurity phases as well as their ferromagnetic contribution.…”
Section: ■ Experimental Results and Discussionmentioning
confidence: 99%
“…Bismuth orthoniobate (BiNbO 4 ) is still of interest after more than half a century due to its microwave dielectric and photocatalytic properties. , BiNbO 4 ceramics containing V 2 O 5 and CuO have excellent dielectric properties, as was shown for the first time in the work revealing high values of the quality factor Q r = 4260 (at 4.3 GHz), dielectric constant ε r = 43, and the coefficient of resonant frequency t f = +38 ppm/°C. In order to obtain high-density ceramics and optimize the dielectric properties of bismuth orthoniobate, sintering additives are added and bismuth or niobium atoms are substituted hetero- and isovalently. The low temperature of the synthesis (∼1000 °C) of bismuth orthoniobate materials promotes their use as dielectrics for multilayer microwave circuits with silver (copper) inner conductors. Thus, bismuth orthoniobate materials facilitate miniaturization of the resonant devices…”
Section: Introductionmentioning
confidence: 99%
“…В формуле (1) независимыми параметрами являются доли кластеров с ферро-и антиферромагнитным типом взаимодействия, а также неявно входящие в формулу параметры ферро -и антиферромагнитного обмена между атомами железа (III) в димерах и тримерах. Формулы для расчета магнитной восприимчивости димеров и тримеров по модели Гейзенберга-Дирака-Ван-Флека [24] и согласования рассчитанных и экспериментальных значений магнитной восприимчивости твердых растворов приведены в работах [18,19].…”
Section: результаты и обсуждениеunclassified